2007
DOI: 10.1007/s11207-007-9071-x
|View full text |Cite
|
Sign up to set email alerts
|

Peak-Size Distributions of Proton Fluxes and Associated Soft X-Ray Flares

Abstract: A database combining information about solar proton enhancements (SPEs) near the Earth and soft X-ray flares (GOES measurements) has been used for the study of different correlations through the period from 1975 to May 2006. The emphasis of this work is on the treatment of peak-size distributions of SXR flares and SPEs. The frequency of SXR flares and solar proton events (>10 and >100 MeV, respectively) for the past three solar cycles has been found to follow mainly a power-law distribution over three to five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 26 publications
2
47
2
Order By: Relevance
“…The size distribution of SEP events has often been characterized in terms of a powerlaw in the peak proton flux or fluence and then compared to the peak soft X-ray (SXR) flux in flares (see, e.g., Hudson 1978;Belov et al 2007;, and references therein). However, the power-law characterizing SEP size is significantly flatter than that of the SXR flux.…”
Section: Size Distribution Of Sep Eventsmentioning
confidence: 99%
“…The size distribution of SEP events has often been characterized in terms of a powerlaw in the peak proton flux or fluence and then compared to the peak soft X-ray (SXR) flux in flares (see, e.g., Hudson 1978;Belov et al 2007;, and references therein). However, the power-law characterizing SEP size is significantly flatter than that of the SXR flux.…”
Section: Size Distribution Of Sep Eventsmentioning
confidence: 99%
“…Energetic particles from stellar eruptive events are not frequently included in these energy budgets, because there are no observational constraints for stars other than the Sun. Existing solar correlations between SXRs and protons detected near Earth (i.e., Belov et al 2007;Cliver et al 2012) cannot be directly applied to HSTʼs UV flares, because we do not know the energy partition between stellar UV emission lines and SXRs during flares. Thus, we have developed a new scaling relation between energetic protons detected near Earth and UV flares from the Sun.…”
Section: Energetic Proton Estimation From Uv Flaresmentioning
confidence: 99%
“…Despite the widespread belief that large SEP events result from particle acceleration at CME shocks, soft X-ray burst characteristics play an important part in operational models used for SEP forecasting (Garcia, 2004;Balch, 2008). Indeed Belov et al (2007) showed that the probability of an SEP event rises with the peak soft X-ray flux of the flare. But they also demonstrated (their Figure 3) that more than 30% of GOES X class flares westward of longitude E 20 • have no SEP event associated with them.…”
Section: Soft X-ray Bursts and Sep Forecastingmentioning
confidence: 99%